Suppressing Divorce with Stoicism - Asikin, Zainal; Hamid, Abd. Rahman; Akmansyah, Muhammad; Anshori, M. Afif (Nizham Jurnal Studi Keislaman, 2025)
The persistently high divorce rate in Indonesia indicates a lack of effective psychological frameworks for sustaining marital stability. Despite numerous interventions, few have integrated philosophical approaches to strengthen emotional resilience in marriage. This study aims to address this gap by exploring the application of Stoic principles as a means of reducing divorce rates through the enhancement of couples’ psychological and emotional endurance. Employing a qualitative design, while qualitative insights were obtained via in-depth interviews and case studies. The findings reveal that Stoic value significantly contribute to constructive conflict management, effective communication, and greater tolerance of differences. Moreover, statistical analysis shows a positive correlation between the application of Stoic principles and marital satisfaction, accompanied by a reduction in divorce intentions. The study concludes by recommending the integration of Stoic-based emotional training into premarital education and marriage counseling programs to promote emotionally resilient and harmonious families in the complexities of modern life.